2009
DOI: 10.1111/j.1365-2702.2009.02943.x
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the continuing professional development needs of nurse independent prescribers and nurse supplementary prescribers who prescribe medicines for patients with diabetes

Abstract: University, for producing the statistical analysis reports 2 ABSTRACT BackgroundNurse Independent and Nurse Supplementary Prescribing has extended the role that nurses in the UK have in the management of care for patients with diabetes. Concerns surround nurses' pharmacological knowledge and provision of continuing professional development (CPD) to meet the needs of nurse prescribers. AimTo examine the CPD needs of nurses who prescribe medicines to patients with diabetes MethodsThe NMC database was used to ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Nevertheless, a number of recurring themes could be discerned, such as the views of nurses, doctors and other parties involved concerning nurse prescribing [45,47,51,53,81,94,108,109,115,121,139], prescribing behaviours of nurses [36,43,124,126,128,129,131,137], and nurse prescribing in relation to specific diseases [38,44,84,89,91-93,101,108,116,125] - most notably concerning nurse prescribing in mental health care [21,32,39,67,76,83,100,102,104-106,132,135]. Also, a number of publications focussed on the history and evolution of (nurse) prescribing of medicines, but these remained relatively limited [5,6,46,48,49,75,90,96,103,142].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a number of recurring themes could be discerned, such as the views of nurses, doctors and other parties involved concerning nurse prescribing [45,47,51,53,81,94,108,109,115,121,139], prescribing behaviours of nurses [36,43,124,126,128,129,131,137], and nurse prescribing in relation to specific diseases [38,44,84,89,91-93,101,108,116,125] - most notably concerning nurse prescribing in mental health care [21,32,39,67,76,83,100,102,104-106,132,135]. Also, a number of publications focussed on the history and evolution of (nurse) prescribing of medicines, but these remained relatively limited [5,6,46,48,49,75,90,96,103,142].…”
Section: Resultsmentioning
confidence: 99%
“…The objective of creating quicker and more efficient patient access to medicines has also been highly influential in the introduction process of nurse prescribing internationally, especially within the UK and Ireland [21,25,26,29,31,32,34-37,39,42,46,47,51,52,55,58,61,62,64,67,69,76,82-84,87,89,90,94,100,102,104,106,112,114][116,120,128,132,135-137,140]. Another important force in this process has been the aim to make better use of nurses' skills and knowledge, and to improve the use of both health professionals' and patients' time [5,6,23,26,30,34,37,39,41,42,44,46,47,51,52,55,56,60,64,66-69,73-76,79,84,86,87,89,90,92,93,100,102,103,106,109][115-118,124,125,130,132-134,137]. Whereas these seem to have been the main drivers behind the introduction of nurse prescribing in the UK and Ireland, forces originating from within the health professions appear to have prevailed in other countries.…”
Section: Resultsmentioning
confidence: 99%
“…While a multidisciplinary approach to the management of diabetic foot disease is preferred, there is evidence that nurses play a key role in the prevention and control of diabetes complications (Carey & Courtenay 2010). Although much effort has been expended in developing the competence of nurses in diabetes care (Carey & Courtenay 2010), little is known about their level of foot care knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Although much effort has been expended in developing the competence of nurses in diabetes care (Carey & Courtenay 2010), little is known about their level of foot care knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…In a study on nurse-independent prescribers, the participants were asked to give reasons why they were unable to access Continuous Professional Development; they revealed that there was a lack of funding from their employer (Carey & Courtenay, 2009). In a summer internship programme run for senior nursing students in Kansas the hospital paid all tuition fees, on condition that they worked back at least a year after they registered as nurses.…”
Section: They Commented As Followsmentioning
confidence: 99%